Forensic Analysis of the WhatsApp Application Using the National Institute of Justice Framework - Muhammad Fahmi Mubarok Nahdli; Muhammad Kunta Biddinika; Imam Riadi (International Journal of Advances in Data and Information Systems, 2024)
The advancement of communication media has rapidly evolved with the emergence of various communication applications on smartphones, which have now surpassed mere communication functions to become complex social media platforms. This change has transformed the way we interact, not only through messages and voice but also through the exchange of videos and images. However, along with these developments, there has been a surge in digital crimes such as defamation, fraud, and drug trafficking. This investigation aims to compare the performance of forensic tools in obtaining digital evidence by utilizing applications like Mobiledit, Belkasoft, Mobile Forensic SPF, and Magnet Axiom, and by applying the National Institute of Justice framework, which consists of five stages: identification, collection, examination, analysis, and reporting. The output of the investigation is presented through reports and evidence, resulting in text chat files, contacts, images, audio, and view-once images. Forensic tools have a 100% success rate in finding pieces of evidence. The comparison of the four tools showed different percentages: Mobiledit Forensic 40%, Magnet Axiom 80%, Belkasoft 60%, and Mobile Forensic SPF 60% in obtaining evidence. Digital evidence can be used as strong support in court proceedings.